Revocation of Political Rights Convicted of Corruption In Every Judge's Decision as An Effort to Eradicate Corruption - Irsan Rahman; L. M. Ricard Zeldi Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The source of political rights inherent in human rights and political rights are also closely related to power. Meanwhile, corruptors who abuse their power are only sentenced to an average of 2 years and 2 months in prison during 2016; In 2013 the average sentence was 2 years 11 months; in 2014 2 years 8 months; and 2015 only 2 years 2 months. There needs to be a formulation of the provisions of the regulations as a basis for integrating and harmonizing judges' decisions on the revocation of political rights or it is also necessary to formulate a special criminal system to eradicate corruption crimes. Therefore, this study aims to examine what things underlie the enforcement of the deprivation of the political rights of the convicted of corruption in judge's decision and formulation of the criminal law system regarding the deprivation of political rights of convicted of corruption in judge's decision?. This research was conducted using a type of sociological juridical research approach. The result of the research is the abolition of political rights for corruption convicts, when examined from the juridical, sociological, and human rights aspects. It must become a standard in the punishment of corruption, considering that several formulations of the criminal law system currently exist in the criminal act of corruption which is still relatively light because the several sanctions given to date have not minimized acts of corruption.